1992
DOI: 10.1346/ccmn.1992.0400506
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fe(II) on the Formation of the Spinel Iron Oxide in Alkaline Medium

Abstract: Fe(II) and Fe(III) in various proportions were coprecipitated by NH3 at pH ≈ 11. The Fe(II)/Fe(III) ratio (x) was varied from 0.10 to 0.50. After stabilization by aging at pH ≃ 8 in anaerobic conditions, hydrous precipitates were characterized by electron microscopy, Mössbauer spectroscopy, and kinetics of dissolution in acidic medium. At any x value, all stable products exhibited the structure of (oxidized) magnetite. For x ≤ 0.30, two distinct species were coexisting: the one (“m”) was made up of ca. 4nm-siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
94
1
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 25 publications
13
94
1
4
Order By: Relevance
“…The sextet #2 (octahedral) for the 0.001 and 0.054 Als samples at 77 K is Fe 3 § as these samples are highly oxidized (note the low value of IS compared with 0.152 and 0.20 A1s), and the 0 mole % At sample has the two overlapping sextets characteristic of maghemite rather than magnetite (consistent with its greater oxidation). Jolivet et al (1992) in preparing magnetite in a similar fashion to what we have done, observed the formation of two types of particles, some smaller (~ 4 nm) and others larger ( > 25 nm). The greater the oxidation of Fe 2 § the more of the smaller variety formed.…”
Section: Clays and Clay Mineralssupporting
confidence: 75%
See 3 more Smart Citations
“…The sextet #2 (octahedral) for the 0.001 and 0.054 Als samples at 77 K is Fe 3 § as these samples are highly oxidized (note the low value of IS compared with 0.152 and 0.20 A1s), and the 0 mole % At sample has the two overlapping sextets characteristic of maghemite rather than magnetite (consistent with its greater oxidation). Jolivet et al (1992) in preparing magnetite in a similar fashion to what we have done, observed the formation of two types of particles, some smaller (~ 4 nm) and others larger ( > 25 nm). The greater the oxidation of Fe 2 § the more of the smaller variety formed.…”
Section: Clays and Clay Mineralssupporting
confidence: 75%
“…The ratio Feo/Fed = 0 represents a mature soil, and Feo/Fed = 1 represents an immature soil. As shown in this and other studies (Rhoton et al, 1981;Jolivet et al, 1992), magnetites prepared by precipitation from aqueous solutions (MT-RT samples) have small particle sizes and are strongly cation deficient (partially oxidized). Despite relatively low Fe 2 + contents (< 5 wt.…”
Section: Mt-r T Series Samplessupporting
confidence: 71%
See 2 more Smart Citations
“…Peaks other than 6-line in the difference pattern are artifacts of the subtraction procedure. played a Mössbauer spectrum similar to that of abiotically synthesized magnetite with Fe 2+ /Fe 3+ = 0.25 (Jolivet et al 1992). The central doublet disappeared upon cooling the bioreduced sample to 77 K (Fig.…”
Section: Bioreductive Transformation Of Ni Ferrihydritementioning
confidence: 87%